2002
DOI: 10.1111/1467-9671.00122
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of an Ecological Model and GIS Spatial Analysis to Describe Niche Partitioning Amongst Carrion Beetles in Nebraska

Abstract: Carrion beetles depend on vertebrate carcasses to rear their young. Carcasses are a limited resource with patchy distribution, and there is an intense competition among many species for these carcasses. This situation is expected to lead to niche partitioning, such that different beetle species use different resources and thus escape direct competition. Our project used a geographic information system (GIS) and pitfall sampling to characterize carrion beetle preferences for soil texture and land use in Kearney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Of the seven silphid beetle species identified, they found that three Nicrophorus species, including N. marginatus, were more abundant in loessal soils and two Nicrophorus species were more abundant in granitic soils. Similar niche partitioning associated with soil type was found for several Nebraska burying beetles in areas without ABB presence (Bishop et al, 2002). Soil texture candidate variables were not part of the best subset of variables for the Loess Canyon's ABB suitability models and the region has high silt content, which is very different from the sandy soils of the Sandhills.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Of the seven silphid beetle species identified, they found that three Nicrophorus species, including N. marginatus, were more abundant in loessal soils and two Nicrophorus species were more abundant in granitic soils. Similar niche partitioning associated with soil type was found for several Nebraska burying beetles in areas without ABB presence (Bishop et al, 2002). Soil texture candidate variables were not part of the best subset of variables for the Loess Canyon's ABB suitability models and the region has high silt content, which is very different from the sandy soils of the Sandhills.…”
Section: Discussionsupporting
confidence: 51%
“…These differences could be attributed to soil texture and compaction or other land cover variables. Additional information on the distribution and density of other carrion beetles found in the Sandhills ecoregion could be utilized in future modelling efforts because of the possible influence of niche partitioning (Bishop et al, 2002;Dobesh, 2007). Crawford & Hoagland (2010) pointed out a number of difficulties in modelling ABB occurrence, such as problems determining grain size (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a huge literature on contact zones in a multitude of taxa, and many important papers on the influence of environmental factors (e.g. Reinert, 1984a; Bishop et al ., 2002). However, few studies have addressed this relationship spatially, using Geographical Information System (GIS) tools (but see Anderson et al ., 2002; Swenson, 2006), and usually these studies performed over broad regions, such as continents (but see Brito & Crespo, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Other silphid species (e.g. N. orbicollis ) are found in moister areas, such as forests near water, and are active at night; thus, they may have even higher water‐loss rates (Bishop et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%